MAKNA HIDUP LANJUT USIA DI PANTI JOMPO KHUSNUL KHOTIMAH KOTA PEKANBARU - Syahfitri, Yulisa; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The phenomenon of elderly people in nursing homes has become a phenomenon and social movement. With a variety of reasons behind the elderly to live in nursing homes such as the elderly who do not have children who are unable to find their own food who have asked to eat with their closest neighbors, abandoned by children, want to live in nursing homes because they do not want to trouble children and conflict with family. Elderly people in nursing homes have a strong spirit to survive. Elderly really appreciates the life that is being lived now while in the Technical Implementation Unit of the Social Services of Tresna Werdha (UPT PSTW) in Khusnul Khotimah, Pekanbaru City. The aim of this study was to find out the meaning of the life of the elderly in the Technical Implementation Unit of the Tresna Werdha Social Service (UPT PSTW) of Khusnul Khotimah in Pekanbaru City, to find out the meaning of elderly nursing homes and elderly communication experience.This study uses qualitative research methods with a phenomenological approach. The research subjects consisted of six elderly people in the Khusnul Khotimah nursing home in Pekanbaru City who were selected using a purposive technique. Data collection is done through in-depth interviews, observation and documentation. To do the validity test the author's data was used to extend the participation and triangulation method.The results of this study indicate that the elderly (elderly) interpret the meaning of living in the Khusnul Khotimah nursing home in Pekanbaru City as (1) life is a test, (2) life is a struggle and (3) life is a choice. The elderly who were in the Khusnul Khotimah nursing home in Pekanbaru City interpreted nursing homes as (1) nursing homes as their own homes (2) nursing homes as a favor of Allah SWT (3) nursing homes in return from Allah SWT. The experience of elderly communication in the Khusnul Khotimah nursing home in Pekanbaru City is divided into verbal communication experiences and pleasant and unpleasant non-verbal communication experiences.Keywords : mean, elderly, nursing home